Optimizations of Reaction Parameters of Microwave Enhanced Synthesis of 4,4¦-Dihydroxychalcone - SHARMA, BHAVANA (Asian Journal of Chemistry, 2010)
Different reaction parameters of microwave enhanced synthesis of 4,4´-dihydroxychalcone have been optimized. The variations in reaction time as well as in yield of resulting compound under different set of reaction conditions have also been examined. The structure of 4,4´- hydroxychalcone has been established on the basis of its spectral data.